KONTRIBUSI KONSUMSI MEDIA MASSA TERHADAP PEMANFAATAN TEKNOLOGI INFORMASI DAN TINGKAT MODERNITAS GENERASI MUDA KOTA - Dalyono, C. Teguh (2009)
The aim of this study is to investigate the extent of utilization of information technology (IT) and the level of modernity of the young generation as well as the contribution of socioeconomic status, knowledge of IT, and media consumption on the level of IT utilization and the level of modernity of the urban youth. Data were collected through a set of questionnaires and tests. The subjects of this research were 400 students from seven universities in Yogyakarta, both public and private universities. The data obtained were analyzed by Chi-square test, Kruskal-Wallis, Pearson Product Moment Correlation for descriptive analysis, and multiple regressions for hypothesis testing. The study reveals that the majority of the participants (65.3%) use IT just for their personal needs, especially for communication and entertainment, which are lifestyle oriented. In addition, in terms of modernity level, most of the subjects (71.5%) are at the adaptive modern level, reflected in the fact that they always follow the current changes in lifestyle, have moderate critical attitudes, but show fair tolerance. The results indicate that mass media consumption appears to give the highest contribution significantly to both the use of IT and the level of modernity; family socioeconomic status is found to considerably contribute to the utilization of IT, but not to the level of modernity; and IT knowledge has little contribution toward the use of IT and the level of modernity.